Effect of spraying of fine water particles on facial skin moisture and viscoelasticity in adult women. Issue 3 (6th November 2018) - Nishimura, Naoki; Inoue, Shinsuke; Yokoyama, Keiko; Iwase, Satoshi
Abstract: Background/purpose: It is known that the elderly and adult women with reduction in sebum secretion have reduced skin barrier function, drying of the skin in a low humidity environment is accompanied by physiological distress. As our hypothesis, when fine water particles are sprayed on the skin, the water content of the corneal layer is significantly increased. In the present study, we examined the ability of fine water particles to improve facial skin moisture levels in adult women. Methods: We examined skin conductance, transepidermal water loss (TEWL), and skin elasticity as an index of skin barrier function at the cheek in 17 healthy adult women in the spraying of fine water particles, in the environment temperature at 24°C and 34.5% relative humidity. Results: The skin conductance of stratum corneum after 120 minute of spraying, A condition (peak particle size below 0.5 μm) was 119.7 ± 25.1%, B condition (peak particle size 1.8 μm) was 100.4 ± 31.7%, C condition (peak particle size 5.4 μm) was 110.1 ± 25.0%, and the A condition was significantly higher than the B condition. Also, skin elasticity in the A condition tended to be higher value than in the other conditions. Transepidermal water loss (TEWL) after 120 minute of spraying showed a lower value in the A condition than in the other conditions. In the A condition, the skin conductance steadily maintained their initial levels up to 360 minute after spraying. Conclusion: Especially, by spraying smallest fine water particles, skin barrier function at the cheek was improved. These data indicated that non‐charged fine water particles played an important role on moisten skin in a low humidity environment.